Condom use, contraceptive methods, and religiosity among youths of low socioeconomic level - Cerqueira-santos, Elder; Sílvia Koller, Sílvia; Wilcox, Brian (The Spanish Journal of Psychology, 2008)
The purpose of this study was to investigate the relationship between the use of condoms and other contraceptive methods and religiosity/spirituality among youths of a low socioeconomic level in Porto Alegre. 1013 youths, between 12-24 years of age participated, responding to a personal questionnaire containing 109 items. Results show that 53.5% of these youths had already had their first sexual encounter, 55% of which had this experience before the age of 15. The majority (42.8%) claimed to be Catholic, and 26.7% said they believe in God, but were not religious. There appeared no significant difference in the use of condoms in relation to the level of religiosity, however, men used this method more than women to avoid AIDS and as a contraceptive. Women used other contraceptive methods more frequently, and there were no cases of exclusive use of methods permitted by the major religions (natural methods). This study revealed a high level of condom use (more than 80%) among both religious and non-religious youths.